Simultaneous Effect of Darvyadi Kwath In Eczema (Vicharchika) of Diabetic Patient (Madhumeha Roga) (AYUSHDHARA, 2025)
Skin is the largest organ of the body which acts as barrier between the internal tissue and the external environment. Many inter-related factors affect health of skin including nutrition, hygiene, circulation, immunity, long term use of drugs etc. In Ayurveda, all skin diseases are included in Kushta roga. In the presented case of 56yr old female, diagnosed as case of Vicharchika on the basis of symptoms Kandu (itching), Vedana (pain), Twak Vaivarnyata, Rukshta and Pidika (eruption). She had past history of eczema 2 years ago. She took modern medication from 1 year but doesn’t get significant results. At last, she decided to take Ayurvedic treatment for further relief. According to modern science, symptoms and sign of Vicharchika show similarity with eczema. So, patients were diagnosed as case of Vicharchika (eczema) and treat on the line of management of Vicharchika.